FACTORS INFLUENCING EMOTIONAL BEHAVIOR IN ADOLESCENTS: A CROSS SECTIONAL STUDY - Nia Kurniati; Neneng Haryati; Previarsi Rahayu; Aprilina Sartika (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Around 10–20% of adolescents worldwide experience mental health disorders, including emotional problems. In Indonesia, a recent survey showed that approximately 34.9% of adolescents face mental health issues, with 5.5% experiencing a mental disorder in the past 12 months. At the provincial level, for example, in West Java, the reported prevalence of emotional disorders in adolescents is around 12.1%. This study aimed to identify factors influencing emotional behavior in adolescents, including age, gender, parenting style, and social environment. The research design used in this study was cross-sectional. The sample size was 81 people, and the sampling technique was purposive. Data were collected using the Strengths and Difficulties Questionnaire (SDQ) and a parenting style questionnaire. The Chi-Square test showed significant relationships between emotional behavior and age (p=0.031), gender (p=0.012), parenting style (p=0.004), and social environment (p=0.032). It can be concluded that adolescent emotional behavior is influenced by both internal and external factors. A holistic approach is essential to promote healthy emotional development. Further studies are recommended to explore additional contributing factors